The best book of spaceships - Graham, Ian, 1953-; Bines, Gary; Gibbons, Lee; Llewellyn, Ceri (New York : Kingfisher, 1998)
Illustrations and text describe how humans have tried to learn more about space and some of the equipment and vehicles used to do this.
Includes index.
School Library Journal, March 1999.
Teacher Librarian, December 1999.
School Library Journal.
Teacher Librarian.
5.4
Keywords: Space vehicles -- Juvenile literature; Space vehicles; Space vehicles; Space vehicles; Outer space -- Exploration; Outer space -- Exploration; Outer space -- Exploration